An individual perspective on psychological safety: The role of basic need satisfaction and self-compassion - Wouters-Soomers, Lies; Van Ruysseveldt, Joris; Bos, Arjan E. R.; Jacobs, Nele (Frontiers in Psychology, 2022)
Psychological safety is important for the well-being and productivity of people in the workplace. Psychological safety becomes even more important and even more difficult to maintain in times of uncertainty. Previous research mainly focused on the influence of and on interpersonal relationships. This study applies an individual perspective by investigating what is needed on an individual level in order to build psychological safety. The expectation was that self-compassion induces an individual to experience higher positive affect, and this advances the development of positive relations and social acceptance. Moreover, we assumed that the mediation of the relationship between self-compassion and positive relations and social acceptance by positive affect is moderated by the level of basic need satisfaction. Participants (N= 560) from the Netherlands and Belgium completed an online questionnaire about their level of self-compassion, basic need satisfaction, positive affect and positive relations and social acceptance. Using hierarchical regression analyses for moderated mediation analysis, results showed that self-compassion and positive affect had a significant positive effect on positive relations and social acceptance. Positive affect significantly mediated the relationship between self-compassion and positive relations and social acceptance, when basic need satisfaction was low, but not when basic need satisfaction was high. Our research showed that individuals need either their basic needs satisfied or self-compassion so they can build the high-quality relations needed to stimulate psychological safety. This finding shifts attention from the dyadic relationship to the individual and highlights important factors at the individual level which advance the development of high-quality relationships with others.